Indigenous writings from the convent : negotiating ethnic autonomy in colonial Mexico - Díaz, Mónica, 1974- (First peoples (2010), 2010)
"Diaz has done a very good job of acknowledging precursive and pioneering works in history, literature, and ethnic studies while establishing her own critical originality. Her occupation of a cultural studies viewpoint is in contrast to previous studies by both historians and literary critics, supporting her conclusions and opening new lines of dialogue."--Jennifer L. Eich, author of The Other Mexican Muse: Sor Maria Anna Agueda de San Ignacio (1695-1756)